Systematics and phylogenetic position of the genus Tricirronema Siddiqi, 1993 (Cephalobomorpha) (Journal of Nematode Morphology and Systematics, 2012)
Populations ofTricirronema tentaculatum Siddiqi, 1993 from Vietnam and Cameroon and Tricirronema trifilum Siddiqi, 1993 from New Zealand are described, the latter being a new distribution record for the genus. The phylogenetic relationships of the T. trifilum isolate from New Zealand were inferred from the secondary structure based alignment of the 5 end region of large subunit rDNA sequences (D1/D2/D3 domains of the 28S gene), including 37 selected species of Rhabditida. Maximum likelihood and Bayesian inference resolve Tricirronema as nested within Cephalobidae and group it with the genus Pseudacrobeles with high (>99%) bootstrap support. This result contradicts current morphology-based classification and draws into question the validity of the family Bicirronematidae. It is also included in this analyses the first available sequence of the genus Deficephalobus, representing the equally poorly known family Osstellidae, and the results obtained suggest that it too is actually positioned deep within Cephalobidae, near Pseudacrobeles and Tricirronema.